The Relationship Between Screen Time, Sleep and Obesity - Dominika Lewandowska; Dominika Rosińska-Lewandoska; Zofia Podraza; Dominika Strep; Julia Grabowska; Jakub Rosiński; Zofia Głowniak; Maciej Kwiatkowski; Izabela Kwiatkowska; Malwina Soja (Journal of Education, Health and Sport)
Introduction